PELATIHAN PEMROGRAMAN KOMPUTER DENGAN VISUAL BASIC PADA SISWA SMK PANGUDI LUHUR MUNTILAN - Budi Sugiharto; FA. Rusdi Sambada; Doddy Purwadianto; Wibowo Kusbandono (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2021)
Computer programming is the implementation of a logical and coherent way of thinking even in simple problems. Computer programming training with visual basic is one way to take advantage of existing facilities in Microsoft Excel with a more attractive appearance so that it improves the way students learn. The training was carried out with participants of class X Automotive Light Vehicle Engineering Skills at Pangudi Luhur Muntilan Vocational School. The results of this training, students feel that this training is very useful, interesting, suitable, increases motivation to learn and adds insight or provisions after graduation.